Consumer Intention And Perceptions In Online Purchasing Of Vegetables And Fruit - Esi Asyani Listyowati; Ani Suryantini; Irham Irham (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Internet technology has changed the shopping behavior of consumers in the world including Indonesia as a developing country. Consumers only have to be connected to internet or online to get the product they want without having to go to the seller directly. Consumers buy online because of a good perception of the use of internet technology to meet the needs of vegetables and fruit. This study aimed to understand the level of intention of Indonesian consumers, determine the perceived usefulness, perceived ease of use, perceived of trust, perceived of risk prevention, and perceived of prices of Indonesian consumers in buying fresh agricultural products via online, which were vegetable and fruit. The method of research data analysis used was descriptive analysis. The samples in this study were 146 respondents which obtained by purposive sampling, which was individual who had bought vegetable and fruit via online at least once from various internet-connected applications. The results showed that according to the use of internet technology consumers felt the benefit in finding product information faster, independence in transactions, trusting that the business identity of the online sellers was conveyed honestly, online sellers sent products at the correct address, vegetable and fruit prices set by online sellers in accordance with the benefits received.